Is sCD163 a Clinical Significant Prognostic Value in Cancers? A Systematic Review and Meta-Analysis - Qian, Shushu; Zhang, Hong; Dai, Huibo; Ma, Bangyun; Tian, Fang; Jiang, PengJun; Gao, Haoran; Sha, Xiaocao; Sun, Xuemei (Frontiers in Oncology, 2020)
Background Tumor associated macrophages (TAMs), a kind of inflammatory cells in the tumor microenvironment, are crucial for the occurrence and development of various tumors which increased the expression of CD163. Nevertheless, not much has been established regarding soluble CD163 and its connection to tumor diagnosis. In this case, a meta-analysis was conducted to determine the tumor diagnostic importance of serum sCD163. Methods In order to assess the correlation between sCD163 and the overall survival (OS) or progression-free survival (PFS) among tumor patients, a systematic perusal of literature published until June 2020 was conducted. Relevant data were primarily obtained from papers that have the following qualifications: 1) a confidence interval (CI) of 95%; 2) a report of the hazard ratios; and, 3) pooled by means of the Mantel–Haenszel random-effect representation. Results For the final meta-analysis, eight papers comprised of 1,236 cases were involved. Through pooled investigation, it was determined that a correlation exists between elevated serum sCD163 and worse OS (HR = 2.24, 95% CI: 1.50–3.35, P < 0.001) and PFS (HR = 3.90, 95% CI: 2.33–6.52, P < 0.001) among tumor cases. Subgroup analysis stratified by medium age at diagnosis demonstrated that patients over 60 years old with high sCD163 had worse OS (HR 2.28, 95% CI: 1.58–3.29, P < 0.001) than under 60 (HR 1.43, 95% CI: 1.15–1.77, P = 0.001). Subgroup analysis revealed that analysis method and medium age at diagnosis were the potential source of heterogeneity. Conclusions Overall, diagnosis of tumor cases can be adversely determined through substantial sCD163 levels. Consequently, it is encouraged that extensive researches regarding the rates of cancer survival be accomplished.